OP110 Survey Of Health Technology Assessment Evaluation Strategies For Patient And Public Involvement. (2017) - Weeks, Laura; Polisena, Julie; Scott, Anna; Holtorf, Anke-Peggy; Staniszewska, Sophie; Facey, Karen
Abstract : INTRODUCTION: Although there is increased awareness of patient and public involvement (PPI) among Health Technology Assessment (HTA) organizations, evaluations of PPI initiatives are relatively scarce. Our objective as members of HTAi's Patient and Citizen Involvement Group (PCIG) was to advance understanding of the range of evaluation strategies adopted by HTA organizations and their potential usefulness. METHODS: In March 2016, a survey was sent to HTA organizations through the International Network of Agencies for Health Technology Assessment (INAHTA) and contacts of members of HTAi's PCIG. Respondents were asked about their organizational structure; how patients and members of the public are involved; whether and how PPI initiatives have been evaluated, and, if so, which facilitators and challenges to evaluation were found and how results were used and disseminated. RESULTS: Fifteen programs from twelve countries responded that involved patient (14/15) and members of the public (10/15) in HTA activities. Seven programs evaluated their PPI activities, including participant satisfaction (5/7), process evaluations (5/7) and impact evaluations (4/7). Evaluation results were used to improve PPI activities, identify education and training needs, and direct strategic priorities. Facilitators and challenges revolved around the need for stakeholder buy-in, sufficient resources, senior leadership, and including patients in evaluations. Participants also provided suggestions based on their experiences for others embarking on this work, for example including patients and members of the public in the process. CONCLUSIONS: We identified a small but diverse set of HTA organizations internationally that are evaluating their PPI activities. Our results add to the limited literature by documenting a range of evaluation strategies that reflect the range of rationales and approaches to PPI in HTA. It will be important for HTA organizations to draw on formal evaluation theories and methods when planning future evaluations, and to also share their approaches and experiences with evaluation.